Naruszenie fleksyjności we współczesnym języku rosyjskim z perspektywy typologii systemowej języków Gieorgija P. Mielnikowa - Pstyga, Alicja Teresa; Walentinowa, Olga; Rybakow, Michaił (Przegląd Rusycystyczny, 2019)
The authors of the article discuss from the standpoint of the G.P. Melnikov's systemic typology of languages the phenomena characteristic for speech works of all functional styles of the modern Russian literary language that indicates violation of flectionality of the Russian language. The external preservation of inflexion and grammatical coordination in the event of violation of the forecast function in the designation of cause-effect relationships of the developing events, does not indicate flexiveness.